Respuesta :
IF (x+2) is a factor of the equation, when x=-2, the equation will equal zero...(because the factor equals zero and the equation is the product of its factors and zero times anything is zero.)
3(-2)^3-2(-2)^2-4
-24-8-4=-36
So (x+2) is not a factor...
3(-2)^3-2(-2)^2-4
-24-8-4=-36
So (x+2) is not a factor...
Recall the Factor theorem.
"A polynomial [tex]f(x)[/tex] has a factor [tex](x - k)[/tex] if and only if [tex]f(k) = 0[/tex]"
Thus, let's convert that into what we know here.
[tex]f(x) = 3x^{3} - 2x^{2} - 4[/tex]
A polynomial [tex]f(x)[/tex] has a factor [tex](x - (-2))[/tex] if and only if [tex]f(-2) = 0[/tex]
So, let's substitute -2 in place of x.
[tex]f(-2) = 3(-2)^{3} - 2(-2)^{2} - 4 = -36[/tex]
But [tex]f(-2) \neq 0[/tex], so we can say that [tex](x + 2)[/tex] is not a factor
"A polynomial [tex]f(x)[/tex] has a factor [tex](x - k)[/tex] if and only if [tex]f(k) = 0[/tex]"
Thus, let's convert that into what we know here.
[tex]f(x) = 3x^{3} - 2x^{2} - 4[/tex]
A polynomial [tex]f(x)[/tex] has a factor [tex](x - (-2))[/tex] if and only if [tex]f(-2) = 0[/tex]
So, let's substitute -2 in place of x.
[tex]f(-2) = 3(-2)^{3} - 2(-2)^{2} - 4 = -36[/tex]
But [tex]f(-2) \neq 0[/tex], so we can say that [tex](x + 2)[/tex] is not a factor